The Form of Linguistic Landscape Name and Gala in Lembah Gumanti Subdistrict - Marnisa, Zarwan; Oktavianus, Oktavianus; Revita, Ike (Center of Language and Cultural Studies [CLCS], 2021)
This study aims to describe the form of the linguistic landscape of names and gala in Lembah Gumanti Subdistrict. This research was conducted qualitatively using a linguistic landscape approach. The data in this study are names and gala in public spaces in Lembah Gumanti Subdistrict. The data source is billboards in Lembah Gumanti District. This research data was collected by being photographed using a smartphone and analyzed using the theory of language forms. The method used to analyze the data is the equivalent method. Data is presented using formal and informal methods. After analyzing the data in this study, it was found that the form of language used in the name and gala in Lembah Gumanti Subistrict was generally at the word level for the name which was dominated by a phrase consisting of two words for gala. In addition, the names and gala that appear in public spaces in Lembah Gumanti Subistrict are dominated by noun word classes.